The Effectiveness of Group Video-based Smoking Cessation Strategy (GRACIOUS) on Patient’s Motivation to Quit: A Randomised Study Among High Cardiovascular Risk Smokers - Idris, Nur Suhaila; Othman, Noor Ezzean Ezzati Mohd; Zin, Faridah Mohd; Zainudin, Aida Maziha; Zakaria, Rosnani (Jurnal Kesmas Prima Indonesia, 2025)
Background: Smoking is a major risk factor for cardiovascular disease, particularly in high-risk individuals. This study aimed to evaluate an effectiveness of innovative, tailored group video-based smoking cessation intervention in enhancing knowledge and motivation to quit among high cardiovascular risk smokers. The group video-based programs may offer a flexible, engaging and impactful alternative to traditional in-person interventions. Methods: This was a two-armed, randomized control trial involving 100 high cardiovascular-risk smokers attending the outpatient clinic Hospital Pakar Universiti Sains Malaysia. Participants were randomized into two equally divided groups. The intervention group received a group video-based smoking cessation seminar and standard care, while the control group received only standard care. Knowledge and motivation scores were measured at baseline, 2 weeks, and 8 weeks post-intervention. Results: There was a significant group-time interaction for both knowledge (p<.001, 95% CI) and motivation scores (p<.001, 95% CI) between the intervention and control groups. Both groups showed significant improvements in knowledge and motivation at 2 and 8 weeks compared to baseline (p<0.05, 95% CI), with the intervention group showing a greater mean difference in both scores. Conclusion: The addition of a group video-based smoking cessation strategy to standard care significantly improved knowledge and motivation to quit smoking among high cardiovascular-risk smokers.